IRON FORTIFICATION IN LEAFY VEGETABLES: PRESENT STATUS AND FUTURE POSSIBILITIES - Chatterjee, Ranjit; CHOWDHURY, RIMAN SAHA; DUKPA, PINKEY; THIRUMDASU, RAVI KIRAN (Innovare Journal of Agricultural Sciences, 2016)
ABSTRACT Iron is an essential micronutrient which carries oxygen in the blood. Iron deficiency anemia is a worldwide health problem especially for women and children. There are two forms of iron-heme and non-heme. The iron in meat is about 40 percent heme and 60 percent non-heme. Much of the iron in the vegetarian diet, however, is in the non-heme from. Vegetarian people, requires 1.8 times more iron compare to non-vegetarian people. Dark green leafy vegetables are the valuable sources of iron, even better on a per calorie basis than meat. Many local, wild and underexploited green leafy vegetables are the good supplier of iron and other valuable micronutrients. They are short duration in nature and accumulates higher amount of biomass within small life periods without much care and precaution. An increase in iron content of up to 3 mg/100 g was obtained in some bio-fortified leafy vegetable. This was about 40 times higher than the traditional leafy vegetable. The best ways for iron fortification in commonly grown leafy vegetables is through agronomic practices or breeding approaches. Increasing iron levels through supplementation of iron containing fertilizer, bio fertilizer or microbial inoculants is the widespread iron-acquisition strategy in plants. It is the safer and effective method to supplement iron and to prevent iron deficiency in different parts of the world. Identification, development and promotion of iron rich leafy vegetable varieties could increase the iron status and its bio-availability in daily diet which will help in reducing the emerging iron deficiency anemia among the women and children throughout the world. Key word: Iron deficiency, green leafy vegetables, iron bio-fortification.